Verification of safety integrity level with the application of Monte Carlo simulation and reliability block diagrams. (May 2016) - Kaczor, Grzegorz; Młynarski, Stanisław; Szkoda, Maciej
Abstract: The paper presents functional safety problems of technical systems. It aims to verify the safety integrity level for a selected integrated safety system. The paper provides a comparative analysis of the safety integrity level with the application of the Monte Carlo simulation and Reliability Block Diagram (RBD) methods. Additionally, a solution is proposed to section off, from the logical structure, so called voting zones to significantly reduce the risk of causing false alarms. The calculations were preceded with a review of existing studies of functional safety in extensive technical systems. The verification was done following the requirements of IEC 61508, which is a commonly accepted standard in the field of functional safety of programmable electronic and control engineering systems. Highlights: The scientific approach covers some practical aspects of SIL verification for the systems with high level of redundancy. The calculations based on Reliability Block Diagrams give less accurate and more pessimistic results of PFH. The Monte Carlo simulation is a universal method for the evaluation of the safety integrity level. Voting zones allows to decrease the amount of false alarms and the costs of system's downtimes.